An Analysis of the Influence of Financial Literacy and Financial Inclusion on the Decision to Use QRIS (Case Study on Brawijaya University Students) - Pinem, Angie Aurea Gustika; Maski, Ghozali (Contemporary Studies in Economic, Finance and Banking, 2025)
In this rapid technological development era, students need to adapt to technology. Quick Response Code Indonesian Standard (QRIS) is a form of innovation in the payment system that has been recognized as effective. Financial literacy is a good provision in using financial inclusion optimally so that people can experience optimal benefits from using financial products, which in this case is QRIS. This research aims to examine the effect of financial literacy and financial inclusion on decisions to use QRIS. The data in this research uses primary data and was obtained by distributing questionnaires to 100 respondents. This research used quantitative analysis methods and was processed using the Smartpls 4.0 tool. The testing in this research used the Structural Equation Modeling analysis method with Partial Least Square (SEM-PLS) with results showing that financial literacy and financial inclusion had a positive and significant effect on the decision to use QRIS.